Maximizing farrowing rate - Levis, D.G. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Farrowing rate can be defined as: 1) the number of mated females that farrow within a contemporary group per total number of MATED females for this group or 2) the number of females that farrow within a contemporary group per total number of EXPOSED females for this group. Generally, the first definition is used when hand-mating, whereas the second definition has to be used when pen-mating. Regardless of the definition, farrowing rate can be maximized only by taking total control of the breeding herd. High farrowing rates will result when fertility is high in boars, sows, and gilts; however, excellent management must be used to maintain high fertility in males and females. North Carolina State University data have shown a high correlation between farrowing rate and live pigs born per bred sow per year (Figure 1). Their data show that for each 10% increase in farrowing rate of bred sows, there is a corresponding increase of 2.63 live pigs born per sow per year. In light of these data, pork producers should strive to maximize farrowing rate. This can be done by providing good management during prebreeding, breeding, and gestation phases. The purpose of this article is to provide information on possible management practices to use during each of these phases.
Keywords: Swine; Farrowing rate; Sow management; Boar management; Hand-mating